Efektifitas Penggunaan Metode Drill Terhadap Peningkatan Hasil Belajar Matematika Pada Siswa Kelas X SMAN 99 Jakarta - Nurhayati Nurhayati; Adi Permana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of the use of the drill method on improving mathematics learning outcomes in grade X students of SMAN 99 Jakarta. The method used in this study is an experimental method with an average difference test analysis. Data collection is carried out by compiling research instruments. An instrument is a special test given to a sample in the form of a test instrument for mathematics learning outcomes. The population was 321 students with a sample of 40 students. The results of the data analysis showed that there was a significant influence on the use of the drill method on improving mathematics learning outcomes in Grade X Students of SMAN 99 Jakarta. It is based on the t-test for Equality of Means 2-way significance value (t-tailed) 0.00 < 0.05 So there is a difference in the real significance of the point score which is meaningful between the Experimental and control groups. The average difference between the groups was 9.8 points where the average experimental group was 79.45 and the control group 69,65.